Effect of PGPR on Growth and Yield of Ginger through Rhizome Rot Management in Eastern Ghat High Land Zone of Odisha - Sunita Behera; Parsuram Sial (International Journal of Economic Plants)
A field experiment was carried out at High Altitude Research Station, Pottangi, Odisha University of Agriculture and Technology, Koraput, Odisha, India during kharif 2018–19 to 2020–21 to study the Effect of Plant Growth Promoting Rhizobacteria in different forms on growth and yield of ginger through soft rot management. The results revealed that % disease intensity has been reduced significantly from 28.10 to 5.9 during the year 2018–2021 in application of Tricho power liquid (T. viride @1×106 cfu ml-1 ) @ 5 ml  l-1 along with basal application @ 5 l bed-1 at 45 and 90 DAS, followed by the application of Tricho capsule (T.harzianum @ 1×106 cfu g-1) @ 1 capsule 120 l-1. of water rhizome treatment for 30 m, basal application at 45 and 90 DAS @ 5 l bed-1, where % disease intensity was 7.1. Similarly fresh rhizome yield increased from 9.6 t ha-1 to 17.6 t ha-1 during the year 2018–2021 in Tricho power liquid (T. viride @ 1×106 cfu ml -1) @ 5 ml l-1 along with basal application @ 5 l bed-1 at 45 and 90 DAS, followed by Tricho capsule (T. harzianum @ 1×106 cfu g-1) @ 1 capsule 120  l-1. of water rhizome treatment for 30 m, basal application at 45 and 90 DAS @ 5 l bed-1) with 15.8 t ha-1 yield.